Use of different information and communication technologies in Indian academic libraries. Issue 1 (2nd February 2015) - Husain, Shabahat; Nazim, Mohammad
Abstract : Purpose: – This paper aims to present an exploration of the potential utilisation of different information and communication technologies (ICT) in Indian academic libraries. Design/methodology/approach: – A survey method was used for the collection of data. A structured questionnaire, containing close-ended questions, was sent by postal mail to 30 librarians of the Central University Libraries in India, of which 15 questionnaires were returned. Findings: – Academic libraries in India have mostly been involved in applying traditional ICT-based solutions for the management of various library functions and services, particularly for organising and retrieving information. Use of modern ICT-based tools of knowledge creation and sharing such as web discovery tools, blogs, wikis, Real Simple Syndication feeds, social networking and social bookmarking seems uncommon in academic libraries. Lack of trained staff in ICT, low level of ICT skills among library users, unawareness of potential benefits of ICT and inadequate ICT infrastructure were found as the major barriers of ICT applications in academic libraries. Practical implications: – Academic libraries in India are still in the early stage of understanding the importance of modern ICTs. Librarians should renovate existing library environment and develop knowledge and skills among their staff in the fields of computer programming, website or portal development, hardware maintenance and metadata or e-resource management for providing quality information services to their users. Originality/value: – Because no empirical study on the use ICT-based knowledge management (KM) tools in academic libraries in India has been carried out before, this study closes this gap and provides guidelines for practising librarians, policy makers, management and the University Grants Commission of India to promote the use of ICTs in libraries, and to design courses of information communication technology and related skills.